Equivariant degree for Abelian actions. Part III: orthogonal maps - Ize, Jorge; Vignoli, Alfonso (Topological Methods in Nonlinear Analysis, 1999)
The main goal of this paper is to define an equivariant degree theory fororthogonal maps. We apply our degree to study of bifurcations andexistence of solutions of equivariant nonlinear problems.